2023
DOI: 10.3390/cells12131732
|View full text |Cite
|
Sign up to set email alerts
|

Allyl Isothiocianate Induces Ca2+ Signals and Nitric Oxide Release by Inducing Reactive Oxygen Species Production in the Human Cerebrovascular Endothelial Cell Line hCMEC/D3

Abstract: Nitric oxide (NO) represents a crucial mediator to regulate cerebral blood flow (CBF) in the human brain both under basal conditions and in response to somatosensory stimulation. An increase in intracellular Ca2+ concentrations ([Ca2+]i) stimulates the endothelial NO synthase to produce NO in human cerebrovascular endothelial cells. Therefore, targeting the endothelial ion channel machinery could represent a promising strategy to rescue endothelial NO signalling in traumatic brain injury and neurodegenerative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 70 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…TRPA1 channels have also been detected in human cerebrovascular endothelial cells, where they are gated by 4-HNE but not by AITC. However, TRPA1-mediated Ca 2+ sparklets were not investigated in this study [119].…”
Section: Ca 2+ Sparklets In Native Endothelial Cells: Trpv3 Trpv4 And...mentioning
confidence: 94%
See 1 more Smart Citation
“…TRPA1 channels have also been detected in human cerebrovascular endothelial cells, where they are gated by 4-HNE but not by AITC. However, TRPA1-mediated Ca 2+ sparklets were not investigated in this study [119].…”
Section: Ca 2+ Sparklets In Native Endothelial Cells: Trpv3 Trpv4 And...mentioning
confidence: 94%
“…Studies on rodents have shown that SK Ca /IK Ca channel currents were detectable in freshly isolated mesenteric artery endothelial cells [101] and in cerebral [166] and pulmonary [103] resistance arteries. Conversely, they are absent in mouse capillary endothelial cells [167], although preliminary evidence suggests that they are present at the human BBB [119].…”
Section: Ca 2+ Sparklets and Ca 2+ Pulsars Recruit Sk Ca /Ik Ca Chann...mentioning
confidence: 99%
“…Mouse brain microcirculation has long been investigated to gain cellular and molecular mechanisms that regulate the functions subserved by the human BBB [51,220,240,241]. However, emerging evidence suggests that the blend of ion channels by which CECs detect neuronal activity can differ between mouse and human microvasculature [242][243][244]. Future work could assess whether NMDARs also signal in a flux-independent manner in mouse brain microvascular endothelial cells.…”
Section: Flux-independent Signaling By Nmdars In Human Cecsmentioning
confidence: 99%
“…Novel cyclosporine A analogues that lack immunosuppressant activity, such as Debio025 and NIM811, are currently under investigation. The efficacy of untargeted antioxidant strategies to attenuate ROS overproduction in mitochondria is also limited by their off-targeted effects on cytosolic ROS, which stimulate cellular survival and other primary functions at moderate levels [ 432 , 434 ]. It has been suggested to exploit the highly hyperpolarized ΔΨm to specifically deliver cationic antioxidant molecules into the mitochondrial matrix [ 435 ]; unfortunately, the ΔΨm is rather depolarized in many CVDs [ 432 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%